2018
DOI: 10.2147/jbm.s177203
|View full text |Cite
|
Sign up to set email alerts
|

To test or not: occurrence of sickle cell trait and assessment of the awareness toward its screening among patients attending Magale Health Center IV, Namisindwa District, Eastern Uganda

Abstract: PurposeTo evaluate the occurrence of sickle cell trait (SCT), assess patient awareness and evaluate the performance of a sickle cell hemoglobin-S (dithionate-qualitative solubility) point-of-care test among patients seeking care at Magale Health Center IV, Namisindwa District, Eastern Uganda.Materials and methodsWe conducted a cross sectional study, in which we consecutively enrolled participants aged ≥18 years at Magale Health Center IV. Four milliliters of EDTA blood were collected by venipuncture and screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Only one child was reported to have HbSS giving a prevalence of 0.24% [20]. In a hospital-based cross-sectional study conducted in Eastern Uganda in 2018, Mandu et al reported the prevalence of HbAS to be 4.5% among 242 adults of 18 to 49 years [21]. In the same year, Mpimbaza et al also reported mean prevalences of HbSS and HbAS to be 0.84% and 8.74% respectively, this was a case-control study of 975 children (6 months to less than 10 years) conducted in Jinja Hospital, Eastern Uganda [22].…”
Section: Prevalence In East Africamentioning
confidence: 99%
“…Only one child was reported to have HbSS giving a prevalence of 0.24% [20]. In a hospital-based cross-sectional study conducted in Eastern Uganda in 2018, Mandu et al reported the prevalence of HbAS to be 4.5% among 242 adults of 18 to 49 years [21]. In the same year, Mpimbaza et al also reported mean prevalences of HbSS and HbAS to be 0.84% and 8.74% respectively, this was a case-control study of 975 children (6 months to less than 10 years) conducted in Jinja Hospital, Eastern Uganda [22].…”
Section: Prevalence In East Africamentioning
confidence: 99%